Hybrid Natural Fiber Composites of Polylactic Acid Reinforced with Sisal and Coir Fibers - Wipoo Sriseubsai; Ariya Praemettha (My University, 2024)
This study explored the tensile and impact strength of polylactic acid (PLA) through the incorporation of sisal and coir fibers. Hybrid natural fiber composites were prepared using PLA as the matrix and sisal and coir fibers as the reinforcements. The hybrid composites were prepared with an internal mixer, followed by compression molding. A constrained mixture design was employed to determine the optimal material combinations and their effects on the tensile and impact strength. Confirmatory experiments based on response surface methodology revealed no significant differences in the data means at the 0.05 significance level. PLA reinforced with sisal fibers alone exhibited the highest tensile strength of 75.36 MPa but demonstrated a low impact resistance of 12.94 kJ/m2 at a 95.22:4.78 (PLA:sisal by volume) ratio. Conversely, the maximum impact resistance of 36.71 kJ/m2 was achieved with PLA and coir at the same ratio. An optimal blend, consisting of 95.22% PLA, 0.78% sisal, and 4.0% coir by volume, resulted in a tensile strength of 51.08 MPa and an impact strength of 26.59 kJ/m2, outperforming other mixtures and pure PLA in the mechanical properties. Additionally, water absorption tests showed that reinforcement with sisal and coir fibers increased both water absorption and stability over 60 h.
Keywords: SISAL; Coir; Polylactic Acid; Compression molding; Natural fiber; Natural Fiber Reinforced Composites